2018
DOI: 10.1002/jcb.27195
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic 3‐long noncoding RNA signature for patients with gastric cancer

Abstract: Current studies showed that long noncoding RNAs (lncRNAs) may act as prognostic biomarkers in a variety of cancers. The aim of this study was to identify and assess a prognostic lncRNA signature in patients with gastric carcinoma (GC). LncRNAs expression profiles and corresponding clinicopathological data for 350 patients with GC were obtained from The Cancer Genome Atlas (TCGA), and the least absolute shrinkage and selection operator Cox (LASSO Cox) regression model was used to identify the lncRNA signature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…The nomogram, as a graphical display tool, was convenient to calculate and interpret the predictive results . Therefore the aim of the present study is to develop and validate a prognostic nomogram for OS of HCC patients based on gene expression data identified by a ceRNA regulatory network.…”
Section: Introductionmentioning
confidence: 99%
“…The nomogram, as a graphical display tool, was convenient to calculate and interpret the predictive results . Therefore the aim of the present study is to develop and validate a prognostic nomogram for OS of HCC patients based on gene expression data identified by a ceRNA regulatory network.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA MALAT1 was reported to have malignant status and predicted poor prognosis in glioma [23]. LncRNA SNHG17 was validated to promote the progression of NSCLC and gastric cancer [24,25]. In present study, SNHG17 expression was identified to be elevated in glioma tissues and cell lines.…”
Section: Discussionmentioning
confidence: 57%
“…Aberrant expression of SNHG17 has been reported to play oncogenic role in several cancers by regulating cancer cell proliferation, migration and metastasis [11][12][13]26]. However, the role of SNHG17 in BC is not well known.…”
Section: Discussionmentioning
confidence: 99%